2011
DOI: 10.1016/j.vetmic.2011.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of human and animal tuberculosis in Ibadan, Southwestern Nigeria

Abstract: From 2005 to 2007, Mycobacterium tuberculosis complex (MTC) strains were isolated from cattle, goats and pigs samples collected at the Bodija abattoir and from human samples from tuberculosis patients and livestock traders at the Akinyele cattle market in Ibadan, Southwestern Nigeria. Seventy four isolates obtained from humans (24) and livestock (50) were identified as MTC strains. Thirty two isolates were spoligotyped. Nineteen of these 32 isolates were identified as M. tuberculosis whilst 13 were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 24 publications
(36 reference statements)
6
49
1
1
Order By: Relevance
“…We observed that infections by M. bovis and M. tuberculosis were prevalent in cattle and humans, respectively. This is generally in agreement with what has been observed regarding the host preference of these two members of MTC [33]. However, two isolates of M. bovis were recovered from human sputum, suggesting human exposure to zoonotic TB.…”
Section: Discussionsupporting
confidence: 91%
“…We observed that infections by M. bovis and M. tuberculosis were prevalent in cattle and humans, respectively. This is generally in agreement with what has been observed regarding the host preference of these two members of MTC [33]. However, two isolates of M. bovis were recovered from human sputum, suggesting human exposure to zoonotic TB.…”
Section: Discussionsupporting
confidence: 91%
“…This result was lower than previous reports of prevalence of BTB in neighbouring Nasarawa State where prevalence of 15.08% was reported among cattle population [29], in Taraba State was 2.8% [30], and in other parts of the country such as in abattoirs in Oyo State was 4.47% [15]. Lower prevalence was reported in Ogbomosho, 0.54% [28].…”
Section: Discussioncontrasting
confidence: 62%
“…Bovine tuberculosis was first reported in Nigeria by Manley [14]; since then a lot of information on bovine tuberculosis had been reported [7, 8, 1519], but no information on the economic losses due to condemnation of meat resulting from detection of tuberculosis lesions has been reported. Furthermore, there is no active national bovine tuberculosis surveillance and control at herd level and farms in Nigeria [20].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that all the M. tuberculosis isolates obtained from the cattle with granulomatous lesion detection after the slaughtering belonged to the T1 family in this study matches up with the results of Jenkins et al [21] . It is stated in the studies related to the molecular epidemiology of the M. tuberculosis belonging to the people in our country that the M. tuberculosis Beijing strains have started to be observed at growing rates [17,22,23] .…”
Section: Discussionsupporting
confidence: 92%